Local Handicraft Development Policy Implementation - Ani Heryani (UBL, 2013)
Implementation of development policies determined by the local craft idealized policy, the target group, the implementing organization and the environmental factors. In policy implementation was also associated with a growing factor in the value of both the organization and the implementing organizations target group, this value in the form of attitudes and behaviors of the organization actors can form political values, organizational values, personal values and the values that guide a persons policy in making decisions.Total synergy of policy implementation pattern that has been arranged and the creation of partnerships between the target groups, policy implementers, responsive to the dynamics of the environment and attention to developing the values that are expected to create the establishment craft development towards increased prosperity for the region and the local community in general.